Atributos estructurales, productividad (hojarasca) y fenología del manglar en la Laguna Macoacán, Golfo de México - Torres Velazquez, Jony Ramiro (2017)
Abstract: Mangroves are tropical species established along topographic gradients in coastal areas, where variations in salinity and flooding periods influence the composition and characteristics of primary productivity. In this paper the structural attributes and litter production of mangroves of the Mecoacan lagoon, Gulf of Mexico were evaluated. In six monitoring sites the floristic composition, diameter at breast height (DBH), height, density mature mangrove trees, juveniles, recruits and seedlings, extraction and mortality were determined. Besides, basal area, importance value index (IVI), coverage and Holdridge complexity index, were calculated. Productivity litter of different mangrove species was quantified by trapping capture, while the physico-chemical parameters in surface, interstitial and groundwater were determined by installing piezometers. The study sites in Mecoacan lagoon were classified into two physiographic types: fringe (Boca, Aspoquero, Arrastradero and Pajaral) and basin (Cerros and Mojarrero). 2 854 mature mangrove trees were measured, where 93% belonged to living trees, 4.4% of extracted trees, and 2.6% dead trees standing. The average density was 2 870 mature mangrove trees ha-1. The highest basal area was found in Pajaral (41.7 m-2 h-1). Avicennia germinans (L.) Stearn presented IVI values higher everywhere, for its high relative density. An average cover of 17.5 m2 was registered. The highest rate in complexity was registered in Cerros (27.5). The species showed zonation with salinity levels of interstitial water; A. germinans located in areas of high salinity (hypersalines) while Laguncularia racemosa (L.) Gaertn and Rhizophora mangle L. in areas of lower salinity. Litter production was 5.15 t ha-1 yr-1, it showed a positive correlation with rainfall and high negative correlation with salinity levels and ORP interstitial and groundwater. Results indicate that variability in the composition and structure of mangrove the Mecoacan, is locally determined by the ability to adapt to environmental conditions (salinity, redox potential) and interspecific relationships of the species present.